The construction of the ideal female body: A critical discourse analysis of Malaysian slimming advertisements / Lau Kui Ling - Lau, Kui Ling (2013)
This study examines how slimming advertisements work to frame slimness as the ideal female beauty. To investigate this issue, this study undertakes to analyze two sources of data: slimming advertisements (100 print advertisements altogether) and interviews (40 sets of transcription). The following research questions guide the development of this investigation: 1) How is the ideal female body textually constructed in the selected slimming advertisements? 2) How is the ideal female body visually constructed in the selected slimming advertisements? 3) In what ways are women influenced by the ideology of the ideal female body? Fairclough’s (1995a) three-dimensional conception of discourse is used to see the relationship between three levels of a particular communicative event: discourse-as-text, discourse-as-discursive practice and discourse-as-social practice. This analytical framework helps in answering the research questions. The first level deals with discourse-as-text. The thesis examines how multimodal resources are used in slimming advertisements to construct the ideal female body through language and visuals. The linguistic analysis focuses on the lexical choices which are related to the construction of ideal female body. As for the visual analysis, the images related to the ideal female body are examined using the analytical framework of visual social semiotics (Kress and van Leeuwen, 1996). The second level deals with discourse-as-discursive practice. Here the study deals with the consumption of text in terms of how the respondents are influenced by the ideology of the ideal female body as portrayed in the slimming advertisements. Finally, the level of discourse-as-sociocultural practice is discussed based on the findings in all the three research questions. The ways the slimming advertisements promote the ideology of the ideal female body are seen in the light of sociocultural practices that play the key roles in maintaining, disseminating and propagating the ideology behind the ideal female body. The findings of this study demonstrate that these advertisements offer proof of how slimness is a part of a sociocultural system of representation where female beauty is limited to images of women that focus on the slim ideal. It is part of a sociocultural system in which the ideal female beauty is constructed as a young, slender and shapely body. It is also consolidated into a system of belief that objectifies women and dictates how women should look or not look like. Women are expected to measure up to the social expectations of how they should look like. This is done by constructing, promoting and sustaining false beauty needs. This beauty ideology and belief system, as seen in the interviews, has been internalized by most of the Malaysian women. This study, therefore, is timely and significant as it shows how this ideal female body is a social construction. By examining the ideal female body image from the linguistic and visual social semiotics lens as well as supported with interview data, the integration of different tools of enquiry provides insights into the possible causes leading to body dysmorphic disorders. It is hoped that by highlighting this issue, women will learn not be too gullible to fall prey easily to the ‘promises’ of the slimming products and services. This can help Malaysian women to be aware of these false advertising claims and to challenge the prevailing notions of slimness and beauty. This research also hopes to create awareness and a constructive ‘suspicion’ of all processes of text interpretation, in the particular context, the slimming advertisements.